A Methodological Review on Challenges in Big Data Environment - Singh, Manpreet; Yadav, Rimmy; Ram, Balwinder (IJRDO -Journal of Computer Science Engineering, 2017)
Big data has shown the great potential in optimizing, making decisions, spotting business trends in various fields such as manufacturing, finance, Information Technology. This paper provides a multi- disciplinary overview of the research issues in big data and its techniques, tools and framework related to the privacy , data storage management, network and energy consumption, fault tolerance and data visualizations. Besides this, outcome challenges and opportunities available in this big data platform have made.